TI_GERICHTE 53.2004.21 vom 20. März 2006 , Cancellazione saldo orario negativo di ore d'insegnamento accumulato - TI Tribunale d'appello (2006)
Cancellazione saldo orario negativo di ore d'insegnamento accumulato